Quantifying volume reduction and peak flow mitigation for three bioretention cells in clay soils in northeast Ohio - Winston, Ryan J.; Dorsey, Jay D.; Hunt, William F. (The Science of the total environment, 2016)
Green infrastructure aims to restore watershed hydrologic function by more closely mimicking pre-development groundwater recharge and evapotranspiration (ET). Bioretention has become a popular stormwater control due to its ability to reduce runoff volume through these pathways. Three bioretention cells constructed in low permeability soils in northeast Ohio were monitored for non-winter quantification of inflow, drainage, ET, and exfiltration. The inclusion of an internal water storage (IWS) zone allowed the three cells to reduce runoff by 59%, 42%, and 36% over the monitoring period, in spite of the tight underlying soils. The exfiltration rate and the IWS zone thickness were the primary determinants of volume reduction performance. Post-construction measured drawdown rates were higher than pre-construction soil vertical hydraulic conductivity tests in all cases, due to lateral exfiltration from the IWS zones and ET, which are not typically accounted for in pre-construction soil testing. The minimum rainfall depths required to produce outflow for the three cells were 5.5, 7.4, and 13.8mm. During events with 1-year design rainfall intensities, peak flow reduction varied from 24 to 96%, with the best mitigation during events where peak rainfall rate occurred before the centroid of the rainfall volume, when adequate bowl storage was available to limit overflow. [Display omitted] •Hydrology of bioretention cells constructed in low permeability soils was evaluated.•Lateral exfiltration was the dominant pathway providing volume reduction.•Bioretention cells were able to completely abstract runoff during small storms.•Peak flow was mitigated during 1-year design rainfall intensities.•Results support the resilience of bioretention systems to poor underlying soils.